A Study on the Adaptability of Industry English in Higher Vocational Colleges–Taking the Textbook Construction of English for Water Conservancy Industry as An Example - He, Desheng (Journal of Theory and Practice of Contemporary Education, 2024)
The orientation of vocational colleges determines that the courses they offer should conform to the school running policy of "service oriented and employment oriented" and highlight the characteristics of vocational education. Under the general trend of reform, the English course teaching requirements for higher vocational education has incorporated industry English teaching into the public English Teaching of higher vocational colleges. Many higher vocational colleges have also changed the general English (EGP) teaching situation that did not have a clear career direction in the past, and have successively carried out the teaching reform of English for special purposes (ESP).